Immersion revisited: A review of existing definitions of immersion and their relation to different theories of presence - Nilsson, Niels; Nordahl, Rolf; Serafin, Stefania (Human Technology, 2016)
The term immersion continues to be applied inconsistently within and across different fields of research connected with the study of virtual reality and interactive media. Moreover, immersion is oftentimes used interchangeably with the terms presence and engagement. This article details a review of existing definitions of immersion originating within the study of video games, virtual environments, and literary works of fiction. Based on this review, a three-dimensional taxonomy of the various conceptualizations of immersion is proposed. That is, the existing definitions of immersion may be broadly divided into three categories, each representing a dimension of the taxonomy: immersion as a property of a system, a subjective response to narrative contents, or a subjective response to challenges within the virtual environment. Finally, four distinct theories of presence are introduced and, based on the established taxonomy, we discuss how the individual theories relate to existing definitions of immersion.